C-myc oncogene product P62c-myc in ovarian mucinous neoplasms: immunohistochemical study correlated with malignancy. Issue 2 (February 1989) - Polacarz, S V; Hey, N A; Stephenson, T J; Hill, A S
Abstract : The monoclonal antibody Myc 1-6E10 was used to determine the cellular distribution of the c-myc oncogene product p62c-myc in 60 mucinous ovarian tumours. Three patterns of immunostaining were apparent: (i) nuclear staining alone; (ii) staining of the nucleus and basal cytoplasm; and (iii) staining of the entire cell. Of the 21 cases of mucinous cystadenoma, 11 showed nuclear staining alone, and a further case showed additional weak staining of the basal cytoplasm. Nuclear staining alone was not present in any of the 17 borderline mucinous tumours examined. Strong staining of the nucleus and basal cytoplasm was seen in 16 of these borderline cases, six of which also showed focal staining of the apical cytoplasm. All 22 cases of mucinous cystadenocarcinoma showed staining of the cell nucleus and entire cell cytoplasm. Focal staining of the apical cytoplasm in six of 17 borderline mucinous tumours produced a pattern of c-myc immunostaining similar to that of cystadenocarcinoma. Retrospective analysis of the clinical data showed that no significant differences between patients with borderline tumours of these two categories could be defined. Although immunostaining with Myc 1-6E10 can be used in the categorisation of mucinous ovarian tumours, it is concluded that standard histological criteria are more accurate indicators of tumour behaviour than is an assessment of c-myc expression.